Exploring the Concept of Continuous Midwifery-Led Care and its Dimensions in Prenatal, Perinatal, and Postnatal Periods - azam bagheri; masoumeh simbar; Mansoureh Samimi; Fatemeh Nahidi; Hamid Alavi (Hamadan University of Medical Sciences, 2017)
Introduction: Considering the importance maternal care, this study aimed at exploring the concept of continuous care and its dimensions in prenatal, perinatal, and postnatal periods. Methods: This was a content analysis qualitative study that was performed using semi-structured in depth interviews. Conventional content analysis method was used for data analysis simultaneously data gathering. Different strategies were adopted for ensuring the accuracy and the rigor of the findings such as prolonged engagement with the data and external peer check. The setting of the study was healthcare, hospital and instruction centers of Kashan University of Medical Sciences. The participants included eighteen midwives and five physicians, who had different official positions. Results: The participants' experiences revealed five concepts for the concept of continuous midwifery-led care, which included continuity, the process of care, education and informing, management, and professionalism. Continuity had 3 categories including continuous physical access, continuity of care in different time periods and continuity of a psycho-emotional relationship. Philosophy of continuous care, home care provision and accountability of the process of care were the process of care categories. Continued promotion, target groups of educations, ethics, rights, backing up, implementation of program documentation and follow-up were other categories. Conclusions: Continuous midwifery-led prenatal, perinatal, and postnatal care is a multidimensional and important concept. Given the differences in health infrastructures of different countries as well as the unique characteristics of pregnancy, higher priorities are recommended for continuous midwifery-led care and its dimensions.